1998
DOI: 10.1161/01.cir.97.20.2003
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of In-Stent Neointima, Which Became Thinner and Transparent Over 3 Years

Abstract: The neointima became thick and nontransparent until 6 months and then became thin and transparent by 3 years. We conclude that neointimal remodeling exists after stenting and plays a major role in the alteration of coronary luminal diameter after stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 12 publications
9
54
0
2
Order By: Relevance
“…In the previous studies, MLD was shown to improve from 6 months to 3 to 4 years after coronary stenting or balloon coronary angioplasty, 8,9,17 which was confirmed in this study. Fibrotic scar formation associated with maturation of smooth muscle cells and reduction in matrix proteoglycans was suggested as one of the possible mechanisms of late angiographic regression, protecting the TLs from atherosclerotic progression or plaque rupture after both balloon coronary angioplasty and coronary stenting.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the previous studies, MLD was shown to improve from 6 months to 3 to 4 years after coronary stenting or balloon coronary angioplasty, 8,9,17 which was confirmed in this study. Fibrotic scar formation associated with maturation of smooth muscle cells and reduction in matrix proteoglycans was suggested as one of the possible mechanisms of late angiographic regression, protecting the TLs from atherosclerotic progression or plaque rupture after both balloon coronary angioplasty and coronary stenting.…”
Section: Discussionsupporting
confidence: 88%
“…Medium-term follow-up studies at 3 to 5 years revealed a paucity of late clinical stent-related problems 4 -8 and even angiographic regression of the stented lesions. 8,9 Recently, Choussat et al 10 reported clinical stability of the stented target site at 8 to 10 years after coronary stenting. However, there is still no long-term angiographic data supporting sustained patency of the stented target site and absence of local complications specific for permanent implantation of metallic prosthesis.…”
mentioning
confidence: 99%
“…40 Thinning of the in-stent neointima (increased transparency) 3 years after stenting has been visualized by coronary angioscopy. 41 The present study provides pathological insights into these observations of neointimal regression; beyond 18 months, the stent neointima becomes less cellular (potentially via SMC apoptosis) and richer in type I collagen.…”
Section: Neointimal Regressionmentioning
confidence: 67%
“…Like angioplasty, stent placement also initially stimulates intimal hyperplasia in animal models and human arteries. Intimal atrophy occurs spontaneously in stented arteries after 6 months in humans (Asakura et al 1998) and 2 months in rats (Finn et al 2002, Langeveld et al 2004. At these late times during regression, the extracellular matrix (ECM) shows a relative loss of versican and a gain of collagen compared to earlier times (Chung et al 2002, Finn et al 2002, Langeveld et al 2004, Farb et al 2004.…”
Section: Versican Metabolism In Intimal Regressionmentioning
confidence: 99%